2021
DOI: 10.1186/s12890-021-01711-3
|View full text |Cite
|
Sign up to set email alerts
|

Weighted gene co-expression network analysis to identify key modules and hub genes associated with paucigranulocytic asthma

Abstract: Background Asthma is a heterogeneous disease that can be divided into four inflammatory phenotypes: eosinophilic asthma (EA), neutrophilic asthma (NA), mixed granulocytic asthma (MGA), and paucigranulocytic asthma (PGA). While research has mainly focused on EA and NA, the understanding of PGA is limited. In this study, we aimed to identify underlying mechanisms and hub genes of PGA. Methods Based on the dataset from Gene Expression Omnibus(GEO), we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…We also explored the relationship between IL18R1 expression and airway inflammatory subtypes, which correlated closely with the response to inhaled glucocorticoid therapy. 24 We did not find any differences in IL18R1 expression across the airway inflammatory infiltration subtypes, even after adjusting for asthma severity (Figure 4C−E,H,I). The scRNA results showed that IL18R1 was predominantly expressed in MCs.…”
Section: Il18r1 Expression In Patients With Asthmamentioning
confidence: 75%
See 1 more Smart Citation
“…We also explored the relationship between IL18R1 expression and airway inflammatory subtypes, which correlated closely with the response to inhaled glucocorticoid therapy. 24 We did not find any differences in IL18R1 expression across the airway inflammatory infiltration subtypes, even after adjusting for asthma severity (Figure 4C−E,H,I). The scRNA results showed that IL18R1 was predominantly expressed in MCs.…”
Section: Il18r1 Expression In Patients With Asthmamentioning
confidence: 75%
“…Moreover, IL18R1 expression was slightly increased in uncontrolled or moderate asthma (Figure B,F,K) and significantly increased in severe asthma compared to healthy controls (Figure B,F,K). We also explored the relationship between IL18R1 expression and airway inflammatory subtypes, which correlated closely with the response to inhaled glucocorticoid therapy . We did not find any differences in IL18R1 expression across the airway inflammatory infiltration subtypes, even after adjusting for asthma severity (Figure C–E,H,I).…”
Section: Resultsmentioning
confidence: 94%
“…Further studies showed that this 6 gene expression signature discriminated inflammatory phenotypes in individuals with more severe asthma and in 132 individuals with stable COPD [58,59] . In another transcriptomic analysis, six hub genes central to the PGA phenotype were identified from among 449 differentially expressed genes and were validated in a separate dataset: ADCY2 , CXCL1 , FPRL1 , GPR109B , GPR109A , and ADCY3 [60] . Nearly all of these hub genes are involved in the regulation of immune and inflammatory processes, so their further study may help to explain the weak inflammatory response in PGA.…”
Section: Transcriptomic Definition Of Inflammatory Phenotypesmentioning
confidence: 96%
“…Intrinsic abnormalities in the function of structural cells (such as epithelial cells, smooth muscle cells, vessels and neuronic cells) seem to be pivotal, and these cells seem to orchestrate and preserve airway inflammation [ 19 ] by secreting several paracrine or autocrine factors, which results in the modulation of cellular functions such as agonist-induced shortening, secretion and migration [ 20 ]. Li et al have demonstrated a different gene expression pattern in PGA with moderate discrimination ability, suggesting a decreased immune cell infiltration and function and further supporting the low intensity of the inflammatory process in PGA [ 21 ]. In this study, the genes most relevant to PGA that were detected were ADCY2 , CXCL1 , FPRL1 , GPR109B , GPR109A and ADCY3 , with earlier studies suggesting that ADCY3 upregulation is related to the suppressed function of dendritic cells [ 22 ], whereas the down-regulation of the other five genes has been shown to decrease chemotaxis and immune cell migration to the inflammatory sites [ 23 , 24 , 25 ].…”
Section: Underlying Mechanisms Of Pgamentioning
confidence: 99%